Persepsi masyarakat terhadap program jaminan kesehatan bagi masyarakat miskin - Noviansyah Kristiani, Fatwa Sari Tetra Dewi (Fakultas Kedokteran Universitas Gadjah Mada, 2006)
Background: The perception of community, particularly poor families towards Health Fund for the Poor Program (PJKMM) influences the utilization level of health services. There are internal and external factors influencing the perception, such as education, knowledge, experience, motivation and socialization.Objective: The objective of the study was to get description about the perception of community in Metro City towards PJKMM.Methods: This study was analytical, using cross sectional design, with quantitative and qualitative methods. For quantitative research, 450 respondents were taken as sample using cluster random sampling method. For qualitative research, community, local government officers, and health service providers were chosen as informants. Data were collected by questionnaires and in-depth interview guide. Quantitative data were analyzed statistically by using regression correlation test, Anova, and multivariate analysis using multiple linear regression and partial correlation lest. Qualitative data were analyzed descriptively.Result: 56 % of the respondents had enough knowledge about managed care and 73.3 % of the respondents had neutral perception towards PJKMM. Statistical analysis showed significant correlation between internal factors (formal education, knowledge, experience, and motivation) and perception towards PJKMM